Incommensurate magnetism in non-superconducting PrBa2Cu3O6.92 - Boothroyd, A; Hill, J; McMorrow, D; Andersen, N; Stunault, A; Vettier, C; Wolf, T (1999)
We report the discovery of incommensurate magnetic order in non-superconducting single crystals PrBa2Cu3O6.92. Resonant X-ray magnetic scattering at the Pr L-II and L-III edges and high resolution neutron diffraction were used to characterise the magnetic order on the different magnetic sublattices. The data reveal that the Pr sublattice orders at a temperature of 19 K in an incommensurate structure with ordering wavevector (0.5 +/- delta, 0.5, 0) or (0.5, 0.5 +/- delta, 0), delta approximate to 0.006-0.008, A spin reorientation in the Pr sublattice to a commensurate antiferromagnetic structure with ordering wavevector (0.5, 0.5, 0.5) takes place at a temperature close to 9 K. (C) 1999 Elsevier Science B.V. All rights reserved.